Can Admissions Percent Plans Lead to Better Collegiate Fit for Minority Students? - Cortes, Kalena E.; Lincove, Jane Arnold (American Economic Review, 2016)
Why do so many students mismatch when choosing a college? A plausible hypothesis is a lack of information about the likelihood of admission. This study contributes to the literature on mismatch by testing whether public university automatic admissions policies mitigate academic undermatch and promote academic overmatch by providing some students with admissions certainty. Focusing on the interaction of admissions certainty and race/ethnicity, our results support the hypothesis that a priori admissions information can vastly improve minority access to college quality by encouraging eligible students to apply to, and more importantly, enroll in more challenging institutions.